Effects of sprinter`s ability on gaze motion and cognition during sprint observation - Kurabe, Y.; Nuruki, A.; Ono, K.; Yamazaki, Y.; Ichikawa, H.; Yamashiro, K.; Sato, D.; Maruyama, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Action observation of excellent motion is important to acquire superior skills via the process of motor learning. Good sprint skill is evident in the analysis of elite sprinters such as gold medalists. Many sprinters, however, understand that acquisition of good skill is such a challenge that it can be accomplished only with intense practice. Good sprinters might have abilities to trace significant observation points during observation of performance by other elite sprinters and to enhance sensitivity of cognition for self-awareness. We aimed to compare sprinters and novices in terms of their gaze motion during observation of good sprint presented by a slow-motion video and their expressions of self-awareness to the sprint motion. Methods: Subjects were ten student sprinters aged 18-22 years and eight novices aged 20-22 years. Sprinters was separated into good and poor groups by the result of athlete competition. An eye-gaze tracking system with an infrared light-emitting diode (IR LED) was used to define the coordinate for eye performance during visual sprint observation. The sampling rate (60Hz) was rapid enough to record the smooth-pursuit eye movements covering a 24-inch-wide screen. A sprint converted slow motion (1/10 speed) was presented on the monitor positioned at a distance of 120 cm in front of the subject. The coordinate of the eye movement (resolution, 1024 768 pixels) was superimposed by a synchronous trigger with the slow sprint motion video. We explicitly asked the subjects to concentrate on the images of the motion during the observation. The coordinate of the horizontal axis in the video images was set through a sprint cycle. The coordinate of the vertical axis was divided into three phases as follows: (1) around head, (2) torso and hip, and (3) legs and feet. The number of eye points located in each of the 3 segments were counted throughout the cycle. In addition, we asked the subjects to explain the characteristics of the sprint motion and gaze points of three models of elite sprinters after observation in order to assess the cognition for self-awareness. Results: The good sprinters concentrated about 31% of the gaze points on (3) during a sprint cycle whereas the poor sprinters did about 10% on this segment, respectively. Novices spent about 73% of time on (1) and (2). Good sprinters particularly explained motions occurred in the segment (3) in the interview. The focus of the explanation of the poor sprinters was on either segment (2) or (3). Novices gave their impressions of sprint motions vaguely. Discussion: The differences of gaze motion during sprint observation could reflect the sprinter`s ability and the sensitivity of cognition for selfawareness to sprint motion. The pattern of gaze points for sprint motion would be significant in terms of improving sprint skill via motor learning.